The Relationship Between Loneliness and Quarter Life Crisis in Early Adulthood in Medan City - Malau, Mutiara; Simarmata, Nenny Ika Putri (Jurnal Ilmiah Sumber Daya Manusia, 2024)
Quarter Life Crisis is a situation experienced by individuals entering early adulthood or what is known as the process of emerging adulthood, when they feel pressured by various demands that must be done to become adults. Early adults who experience a quarter life crisis sometimes take steps to withdraw from the environment due to shame, fear, or feeling incompatible with others, resulting in loneliness. The purpose of this study was to determine whether there is a relationship between loneliness and quarter life crisis in early adulthood in Medan City. The subjects in this study were early adults aged 20 to 29 years who were in Medan City, with a sample size of 150 people. This study used a quantitative method with a sampling technique in this study was simple random sampling. The measuring instruments used were the quarter life crisis scale and the loneliness scale version 3 (UCLA). The results of this study indicate that there is a positive relationship between the loneliness variable and the quarter life crisis, with a correlation value of 0.613 with p = 0.000 <0.05, which means that the research hypothesis is accepted. It can be concluded that the higher the loneliness experienced by early adults, the higher the quarter life crisis, conversely, the lower the loneliness, the lower the quarter life crisis in early adults in Medan City.